Tourists' willingness-to-pay for George Town, Penang World Heritage Site conservation - Mohd Ariffin, Noor Fazamimah; Ahmad, Yahaya; Alias, Anuar (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
The purpose of this research is to study the benefits of cultural tourism to the stakeholders for preserving their cultural heritage and to show how these benefits can be captured as well as utilized to justify further investments in the conservation of the George Town, Penang World Heritage Site (GTWHS). The paper attempts to evaluate the tourists’ attitude as well as responses towards the willingness-to-pay (WTP) value for GTWHS conservation. A total of 147 tourists at the George Town Conservation Zone area were interviewed in 2012. The questionnaire was developed based on the credible Contingent Valuation (CV) methodology. The results of the study have revealed that the attitude of the tourists was found to be positive on the importance of the non-use and their WTP value for the conservation of the world cultural heritage. The highest mean WTP value of the cultural heritage among the tourists was RM42.54 per visit and that a majority of 87% of the tourists have stated that they would be willing to pay for the GTWHS conservation. This positive attitude has contributed to a collective sense of responsibility for the World Heritage Site (WHS) and thus could enhance cultural and economic connections between the public, tourists and the heritage. The study has suggested that there should be dialogue, cooperation and collaboration among the various stakeholders involved. Good conservation of heritage site and proper professional management of tourists were found to enhance the benefits from tourism and thus reducing the social impacts on both the site and the host community.